(untitled) (Prithvi Academic Journal, 2022)
Geopolitical and strategic compulsions have posed critical challenges to the national security of Nepal. To safeguard its sovereignty, independence, indivisibility, and international credibility, the slogan of ‘nation first’ must be adopted in the country. We need to strengthen nationalism by reinforcing economic, political, social, cultural, moral, and psychological facets. To repair the damages, we need to devise a process carefully wherein the state actors and non-state actors from formal and informal sectors have a joint coordinated action plan to develop the entire nation as a whole. This research will analyze such socio-political, behavioral, and economic variables, which will assist in finding the gaps in the current system leading to the formulation of an appropriate conceptual approach to strengthening national security strategies. This study applies the qualitative research design and aims to explore the political dynamics in Nepal with an interpretative approach. To substantiate the claims, the researcher uses primary and secondary data from multiple sources. The essence of the subject matter provides a wider domain for future researchers to explore more about this area of study.